NEW RECORD OF SPILOMYIA TRIANGULATA VAN STEENIS, 2000 (DIPTERA: SYRPHIDAE) FROM IRAN (Acta Entomologica Serbica, 2012)
A survey was conducted to identify the hoverflies in Northern Iran during 2010-2011. As a part of this study, Spilomyia triangulata van Steenis, 2000 is recorded for the first time from Iran. Diagnostic characters and geographical distribution of the newly recorded species is briefly discussed. Supplementary photographs of the species are provided.